Green Transformational Leadership and Environmental Outcomes: Empirical Evidence from Food and Beverages Manufacturing Firms in Kwara State, Nigeria - Olanipekun, Lateef Okikiola; Aremo, Michael Olanipekun; Omosanya, Oluwashola Kike; Oderinde, Michael Adekunle (Acta Universitatis Danubius. Œconomica, 2024)
Sustainable environmental practices have constituted one of the numerous challenges bedeviling the process of sustainable development in the twenty first century. This tragedy makes it becomes highly pertinent to raise awareness as a mechanism for combatting environmental menace in a bid to mitigate dysfunctional consequences and one of the potent factors to assist in this regard is having the right leadership in place to steer the ship of instilling eco-friendly attitude and behaviour at work. The study was hinged on the transformational leadership theory and Resource-Based View (RBV) theory respectively. A sample size of one hundred and fifty respondents were selected using the convenience sampling technique and information were obtained through the survey method. The outcome of the study reflected that green-shared vision significantly affected employees’ eco-affable behaviour and green self-efficacy has significant linkage with environmental attitude of the employees. The study concluded that leadership with green philosophies are positive forces for driving the developmental process of sustainable development. Thus, managements should foster an avenue for green oriented leaders to develop employees’ competencies by instilling into them pro-environmental attitude and behaviours necessary for advancing sustainable development